Management of Pancreatic Carcinoma at Al-Thawra Modern General Hospital Sana'a, Yemen - Al-Amry, Ali L.; Shuga'a, Abdul Rahman; Haomash, Nagi; Valenzuela; Al-Washaly, Ahmed; Ateig, Ahmed; Ahmed, Adel (Thamar University Journal of Natural & Applied Sciences, 2023)
Objectives: This descriptive study aims to evaluate surgical management of pancreatic cancer at Al-Thawra Modern General Hospital-Sana’a, Yemen and to provide reflection of clinical presentation and risk factors for pancreatic cancer in Yemen. Methodology:The study was a retrospective descriptive study of forty four patients with pancreatic cancer subjected to surgical treatmentat Al-Thawra Modern general hospital, Sana’a, Yemen over a period from July 2009 to January 2012. Results: Total numbers of patients were 26 males and 18 females with mean age of 62 years. Pancreatic cancers were located in the head of pancreas in 84%, periampulary in 9.1% and 6.8% in the body & tail. Pancreatic cancer was found to be more frequent among smokers 75%. Most patients were presented with obstructive jaundice 81.8%, vague abdominal pain 66% and weight loss 27.3%.Abdominal computer tomography (CT) scanning was done for all cases. Clinical presentation and the accuracy of CT scan in diagnosis and staging of pancreatic cancer are approximately similar to that reported in other countries 81% and 82%. Curative surgical resections were done for 26 cases while palliative surgeries were performed for 18 irresectable cases. Most of complications and all mortality cases occurred among patients who underwent pancreaticoduodenectomy (Whipple operation). However, we reported a higher mortality rate (17.4%) after Whipple operation at Al- Thawra Hospital-Sana’a than other high volume centers. Recommendations: This study recommends multidisciplinary approach for managing pancreatic cancers with liberal use of abdominal CT scan for diagnosis and staging of pancreatic cancers in suspected cases. Meticulous surgical techniques are advised in improving the surgical management of pancreatic cancer with minimal complications. Further extended studies to evaluate the different factors affecting surgery for pancreatic cancers and to provide basis for improvement in the surgical management of pancreatic cancers.